Correlation of International Prostate Symptom Score with Prostate Volume and Intravesical Protrusion of Prostate - Hossain, Md Abul; Islam, Md Waliul; Awal, Md Abdul; Hooda, Md Nurul; Ara, Husne; Naser, Md Fazal; Azam, Md Shafiqul (Bangladesh Journal of Urology, 2020)
Objective: To determine the correlation of international prostate symptom score with prostate volume and Intravesical protrusion of prostate. Methods: This cross-sectional study was performed on 60 elderly patients presented with LUTS suggestive of Benign Enlargement of Prostate. Their evaluation included DRE, IPSS, Uroflowmetry (Qmax), serum PSA measurements and transabdominal ultrasound scan. Statistical analysis was performed by SPSS version 13 using Chi square test and scatter plots together with Spearmna’s correlation coefficients were used to assess the relationship between IPP and PV with IPSS. Results: Mean age of the patients was 66.7+9.85 years, IPSS 23.6+6.53, mean prostatic volume was 60.23+38.16 mL, Qmax 7.98+3.87, PVR was 163.18+141.73 mL. Fifty percent of patients had severe degree (>10mm) of intravesical protrusion of the prostate, 30% had moderate and 20% had mild IPP. There was significant positive correlation between IPSS and PV (r=0.585, P < 0.001), IPSS and IPP (r=0.698, P < 0.001). Conclusion: From this cross-sectional study it is revealed that both the IPP and prostate volume had strong correlation with IPSS, but IPP had stronger correlation with IPSS. Bangladesh Journal of Urology, Vol. 16, No. 2, July 2013 p.43-46